المعوقات الإجتماعية للممارسة المقاولاتية - الأبيض يوسف; قاسمي السعدي هشام; بعداش الطاهر (جامعة عمار ثليجي الاغواط, 2022)
This study seeks to know the social obstacles to entrepreneurial practice in Algeria. Entrepreneurial practice is exposed to problems and obstacles that hinder young people in their practice and make them reluctance to do so despite the existence of projects and ideas they want to achieve. Small and medium enterprises are considered the most effective method in moving the semi-skilled and unskilled workforce towards the industrialization process. , which coincides with the attention that is usually given to two issues: providing job opportunities for individuals who are relatively highly skilled and expanding the scope of industrial development in the economy to include all fields. For this purpose, the current study was applied to a sample of contractors and those related to the entrepreneurial practice, and their number was in 60 individuals, and the questionnaire was distributed to them manually, and 35 forms were retrieved. The results of the study found: • The administrative procedures for establishing a business are considered an obstacle for young people to practice entrepreneurship • The degree of identification of social obstacles that hinder the entrepreneurial orientation does not differ according to age • The degree of identification of social obstacles to entrepreneurship does not differ according to gender • There are human obstacles that hinder the practice of entrepreneurship in Algeria.